TO STUDY INCIDENCE OF MULTI DRUG RESISTANT TUBERCULOSIS IN MUMBAI - Vaidya, Shashikant; Muley, Shreyasi; Kulkarni, Mohan; Koppikar, Geeta (LIFE: International Journal of Health and Life-Sciences, 2015)
Ionized and Rifampicin, the two most potent anti-tuberculosis drugs are rendered ineffective in Multidrug-resistant Tuberculosis (MDR-TB). India, China and Russia contribute to more than 62% of MDR-TB globally. In India, endemic areas like Mumbai are “hotspots” for the dissemination of MDR-TB. The aim of the study was to investigate the incidence of MDR-TB in cases of pulmonary tuberculosis in Mumbai. Total hundred and two clinical isolates of.Tuberculosiswas tested in the study. Drug susceptibility testing of these strains were carried by Resistance Ratio method to ant tuberculosis drugs namely Ionized, Streptomycin andEthambutol and by absolute concentration method for Rifampicinand Pyrazinamide. In our study highest resistance (46 %) was observed to INH followed by RF (42.16 %), SM (29.41 %) and EMB (25.49 %). While, resistance to Pyrazinamide (PZ) was least (7.8%). MDR TB cases were found to be 41.18%.There was significant difference between resistance pattern of INH and EMB, INH and SM, PZ and EMB, PZ and SM, EMB and RF, PZ and RF. (chi square with Yates correction =8.5, p<0.01).Detection of MDR TB strain would not only eliminate non-essential use of antibiotics, but would also help in the selection of most effective drug regimen and guide therapy in chronic cases.